PEMBELAJARAN ALQURAN DI SEKOLAH DASAR ISLAM TERPADU KOTA MEDAN - Abbas, Syamsu Nahar, Mardianto (Pascasarjana UIN Sumatera Utara, 2018)
Abstract: This study aims to determine; 1) Quran learning program in SD IT Siti Hajar, SD IT Al-Munadi, and SD IT Khairul Imam; 2) The implementation of the Qur’an learning that is applied in SDIT Siti Hajar, SDIT Al-Munadi, dan SD IT Khairul Imam; 3) Students’ ability in learning of Qur’an in SDIT Siti Hajar, SD IT Al-Munadi, and SD IT Khairul Imam. This study applied qualitative method. Thefindings of this study are; 1) Qur’an learning programs conducted at the research location are generallyallocated at the same time in the morning with classical patterns; 2) The implementation of Qur’anlearning which is done by SD IT has a variety of alternative methods, students who have not completediqra ‘generally use the Latin memorization method with a repetition system; 3) With daily routines,generally SD IT (Siti Hajar, Al-Munadi, Khairul Imam) is able to complete the specified target, such ascompleting iqra ‘before class 4 (four), the able (tartil) read the Qur’an for grades 5-6, and able tomemorize juz 30. Through this study, The researcher encouraged to give the Qur’an learning to theirchildren from the early age, in addition to their productive age (golden age) as well as the challenges ofthe times which is getters away from Islamic values.Kata Kunci: Home Schooling dan Pembelajaran